Deformation studies on slope area using a digital close range photogrammetry - Syed Yusoff, Sharifah Izyani (2015)
Most of deformation monitoring for slope instability can be supplied important information about slope behavior that can lead to disaster or collapse. This phenomena always occur when monsoon season where persistent rain triggered landslide or floods and because of thus all human activities and development also deforestation is affected as a result of the disaster. Therefore, for safety and maintenance process, it’s important to make sure the stability of the slope area to be monitored. Thus, in order to monitor the movement of slope area, once of the technique are introduced is a Digital Close Range Photogrammetry (CRP) field. The development of photogrammetry nowadays allow to calculate of high accuracy Three-dimensional (3D) coordinates for points on an around the slope area. A side from others technique that was introduces, the CRP technology become getting popular for monitoring slope instability that can lead the disaster. The privilege of using CRP is that no physical contact with the monitoring objects such as slope area body like in conventional land surveying technique. This thesis describes the effectiveness use a digital CRP in deformation studies on slope area. The proposed technique uses a non-metric camera as a tool for capturing slope area images. Before that the camera has been calibrated using calibration sheet provided by PhotoModeler Scanner (PMS) software. The 3D model of slope area has been created using Agisoft software and additional analysis for statistical hypothesis test with Statistical Package for Social Science (SPSS). The selected site has been chosen in Universiti Teknologi Malaysia (UTM) which located at behind the Bioscience and Medical Engineering Faculty building because of there is soil erosion in the area. The Total Station has been used to establish control network points for preliminary results and be continued with Global Positioning Station for the sub control station almost near with slope area. All data processing for CRP image were processed using PMS and Agisoft software. Finally, the 3D digital modelling is presented and the results shows CRP data could be an effective method to monitor deformation studies and capable to achieve a high accuracy compared to others technique.